Early Morning Equatorial Ionization Anomaly From GOLD Observations. Issue 7 (9th July 2020) - Laskar, F. I.; Eastes, R. W.; Martinis, C. R.; Daniell, R. E.; Pedatella, N. M.; Burns, A. G.; McClintock, W.; Goncharenko, L. P.; Coster, A.; Milla, M. A.; Wang, W.; Valladares, C. E.; et al.
Abstract: During geomagnetically quiet and solar minimum conditions, spatial variations of the early morning thermosphere‐ionosphere (TI) system are expected to be mainly governed by wave dynamics. To study the postmidnight dynamical coupling, we investigated the early morning equatorial ionization anomaly (EIA) using Global‐scale Observations of the Limb and Disk (GOLD) measurements of OI‐135.6 nm nightglow emission and global navigation satellite system (GNSS)‐based total electron content (TEC) maps. The EIA structures in the OI‐135.6 nm emission over the American landmass resemble, spatially and temporally, those observed in the GNSS‐TEC maps. The early morning EIA (EM‐EIA) crests are well separated in latitude and mostly located over the middle of South America during October–November. In February–April the crests are less separated in latitude and predominantly located over the west coast sector of South America. Whole Atmosphere Community Climate Model with thermosphere and ionosphere eXtension (WACCMX) simulations with constant solar minimum and quiet‐geomagnetic conditions show that EM‐EIA can occur globally and shows properties similar to longitudinal Wave 4 pattern. Thus, we propose that EM‐EIA is driven by dynamical changes associated with the lower atmospheric waves. Key Points: GOLD observes early morning EIA in OI‐135.6 nm airglow over South America Radiative recombination is the predominant mechanism giving rise to the early morning emissions in the EIA region WACCMX simulations show that early morning EIA can occur globally and has properties similar to longitudinal Wave 4 structure